2021
DOI: 10.5946/ce.2020.121
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection versus Surgery for Undifferentiated-Type Early Gastric Cancer: A Systematic Review and Meta-Analysis

Abstract: Background/Aims The use of endoscopic submucosal dissection (ESD) for treating undifferentiated-type early gastric cancer is controversial. The objective of this study was to perform a meta-analysis to compare the long-term outcomes of ESD and surgery for undifferentiated-type early gastric cancer. Methods The PubMed, Cochrane Library, and EMBASE databases were used to search for relevant studies comparing ESD and surgery for undifferentiated-type early gastric cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In our review, we found that ESD may be as effective as surgery, with similar adjusted all-cause mortality. Our results are consistent with a previous meta-analysis which concluded that ESD has a similar all-cause mortality as gastrectomy in uEGC (28). However, our review has a different methodology, as we excluded patients outside the of expanded criteria.…”
Section: What Is Known In the Literature About The Research Questionsupporting
confidence: 91%
“…In our review, we found that ESD may be as effective as surgery, with similar adjusted all-cause mortality. Our results are consistent with a previous meta-analysis which concluded that ESD has a similar all-cause mortality as gastrectomy in uEGC (28). However, our review has a different methodology, as we excluded patients outside the of expanded criteria.…”
Section: What Is Known In the Literature About The Research Questionsupporting
confidence: 91%
“…In this guideline, we reviewed papers published after the previous edition. To date, there has been no prospective RCT comparing the long-term OS of endoscopic resection with that of gastrectomy with LN dissection, the standard treatment for these indications [ 169 ]. According to retrospective studies, there was no difference between gastrectomy and endoscopic resection in terms of OS, but endoscopic resection had a higher local recurrence rate in terms of recurrence-free survival (RFS), which is consistent with the findings of previous studies [ 144 170 171 ].…”
Section: Endoscopic Treatment ( Flowchart 2 )mentioning
confidence: 99%
“…No significant difference was found in the overall survival rate between the ESD and surgery groups (odds ratio [OR]: 2.29, 95% CI: 0.98–5.36). Nevertheless, ESD was associated with a higher recurrence rate and a lower complete resection rate 22 …”
Section: Endoscopy Versus Surgery For Early Gastric Cancer Treatmentmentioning
confidence: 94%
“…Nevertheless, ESD was associated with a higher recurrence rate and a lower complete resection rate. 22…”
Section: Endoscopy Versus Surgery For Early Gastric Cancer Treatmentmentioning
confidence: 99%